Membangun Konsep Pendidikan dalam Era Multikultural - Author: Mastuhu (Unisia, 2005)
In globalization era, the multi-cultural term really becomes its moment. The people in this era should cooperate each other. Besides, society must appreciate other culture or civilization. The plurality has two sides, on one hand it becomes positive side that possibility people cooperate to reach progress together, on the other hand, it has a negative side, it can cause conflict, war, that can destroy society. The problem in this context is how to change or manage conflict to be positive power for education building, bad becomes good, from good becomes big. In this connection, Islam and Islamic education can play important role